Implementing the last planner TM system in a road construction project in Nigeria / Ograbe Ahiakwo ... [et al.] - Ahiakwo, Ograbe; David, Oloke; Suresh, Subashini; Khatib, Jamal (Faculty of Architecture, Planning & Surveying, 2015)
This paper describes a research investigation into the implementation of the Last Planner System (LPS) in a road construction project. LPS is known to be the most developed practical use of Lean Construction. It focuses on minimising the negative impacts of variability, uncertainties, buffers, making projects more predictable, creating reliable work plans and convalescing collaborative planning. LPS is unpopular in highway and road construction projects, as a lot of case studies have been recorded of its application on infrastructure and building projects as against highway and road projects. However in the road project. In order to achieve this aim, an Action Research strategy is adopted using different data collection methods such as interviews, observation and survey questionnaire. The initial state of production plan reliability within this case project was observed to be highly unreliable with a high degree of variability. However as the implementation commenced, production plans were stabilized with an improved reliability in the schedules. The results from this study demonstrate that although a road construction process is a linear process, a number of benefits were still recorded in terms of improving construction planning and control processes, during the implementation.